2014
DOI: 10.1523/jneurosci.4228-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aging Decreases L-Type Calcium Channel Currents and Pacemaker Firing Fidelity in Substantia Nigra Dopamine Neurons

Abstract: Substantia nigra dopamine neurons are involved in behavioral processes that include cognition, reward learning, and voluntary movement. Selective deterioration of these neurons is responsible for the motor deficits associated with Parkinson's disease (PD). Aging is the leading risk factor for PD, suggesting that adaptations occurring in dopamine neurons during normal aging may predispose individuals to the development of PD. Previous studies suggest that the unique set of ion conductances that drive spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…Ng is also known to be localized to the membrane when it is unbound to CaM (Dominguez-Gonzalez et al, 2007). It is possible Ng-α-syn binding occurs in the presence of calcium, as the studies presented here demonstrate decreased binding in PD correlates with decreased p-Ng as seen in the membrane fraction, indicating the result could be a by-product of calcium disturbances in degeneration (Branch et al, 2014). However, in DLB there is also decreased p-Ng in the membrane, but not decreased Ng-α-syn interaction compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 67%
“…Ng is also known to be localized to the membrane when it is unbound to CaM (Dominguez-Gonzalez et al, 2007). It is possible Ng-α-syn binding occurs in the presence of calcium, as the studies presented here demonstrate decreased binding in PD correlates with decreased p-Ng as seen in the membrane fraction, indicating the result could be a by-product of calcium disturbances in degeneration (Branch et al, 2014). However, in DLB there is also decreased p-Ng in the membrane, but not decreased Ng-α-syn interaction compared to age-matched controls.…”
Section: Discussionmentioning
confidence: 67%
“…On protein level, qualtitative analyses revealed slight differences in hippocampal Cav1.3 expression pattern between age-groups, in that Cav1.3 expression intensity was higher in the dentate gyrus granular layer in middle-aged than in adult animals. Existing data on age-related changes of LTCC expression are conflicting, ranging from increased LTCC expression in the aged brain [41] to no changes [55] or decreased expression [42,43]. This discrepancy may be partly due to different methods of analysis, since Nunez-Santana and colleagues have recently shown that Cav1.2 and Cav1.3 expression in the hippocampus of 32 months old rat is reduced on the protein, but not on the mRNA level [56].…”
Section: Discussionmentioning
confidence: 99%
“…NSCs, NPCs, mature neurons), and which steps in adult neurogenesis (proliferation, cell survival, cell differentiation and fate Page 6 of 37 A c c e p t e d M a n u s c r i p t 6 determination) are affected. Further, the impact of aging on LTCC expression and functionality is still controversially discussed, with some authors reporting increased [41] and others reduced [42,43] LTCC expression levels in the hippocampus of aged animals. To what extent the presumed changes in LTCC properties in the aged hippocampus might contribute to the reduced levels of neurogenesis in aged individuals, has not been addressed so far.…”
Section: Introductionmentioning
confidence: 99%
“…While originally thought to be crucial for the generation of intrinsic pacemaker activity in SN DA neurons (Nedergaard et al 1993;Mercuri et al 1994;Chan et al 2007;Puopolo et al 2007), it is now widely accepted that LTCCs are not essential for SN DA pacemaker activity generation, but are stabilizing pacemaker activity and its precision (Guzman et al 2009;Drion et al 2011;Branch et al 2014 (Platzer et al 2000;Striessnig and Koschak 2008)] by other ion channels, e.g. by functional down-regulation of inhibitory Kv1 potassium channels within minutes after DHP-mediated distortion of SN DA activity, or functional up-regulation of either hyperpolarization-activated cyclic nucleotide-gated (HCN) cation channels, or of TTCCs (Cav3.1) on longer time scales (Chan et al 2007;Guzman et al 2009;Poetschke et al 2015).…”
Section: Cav13 L-type Ca 2+ Channels Stabilize and Stimulate Activitmentioning
confidence: 99%